Urban Wastewater as Hotspot for Antibiotic and Antibiotic Resistant Bacteria Spread into the Aquatic Environment - Ahmad1, Maqsood; U. Khan1, Amin; Wahid2, Abdul; Farhan1, Muhammad; Ali Butt3, Zahid; Ahmad1, Farooq (Asian Journal of Chemistry, 2014)
The present study was under taken to investigate the occurrence of ofloxacin in hospital wastewater, municipal wastewater and in river water receiving the sewage; along with the assessment of antibiotic resistant Salmonella typhimurium (S. typhi) in these waters. Transfer of antibiotic resistance between two different strains of bacteria was also studied. Untreated sewage from the three hospitals (Mayo, Services and Jinnah) directly entering into municipal wastewater and ultimately flows into the river Ravi without any prior treatment. The concentration of ofloxacin in wastewater of the three hospitals was ranged between 10.69 to 30.55 μg mL-1. However, before mixing of the hospital wastewater, concentration of ofloxacin in the three municipal wastewater drains (receiving the wastewater) was ranged between 0.26 to 0.43 μg mL-1. Downstream to the hospitals, increase in concentration was observed and concentration was ranged between 0.54 to 1.29 μg mL-1. The river water was not contaminated with ofloxacin upstream to the city, while a concentration of the antibiotic downstream to the city was 0.067 μg mL-1. All the water samples collected from hospital and municipal wastewater drains were contaminated with S. typhi. It was noted that hospital isolates were more resistant (50 %) to ofloxacin as compare to municipal wastewater isolates (16.7 %). No S. typhi was detected from the river water before entering first municipal wastewater drain from the city. Downstream to first municipal wastewater drain S. typhi were detected and 33 % of them were resistant to ofloxacin. The bacterial isolates isolated from river water downstream to the city were 100 % resistant to the antibiotic. The results of co-culture of ofloxacin resistant S. typhi and ofloxacin sensitive Escherichia coli revealed that the resistant S. typhi were able to transfer the antibiotic resistance to another species.